Pesticide Residues and Harmful Organic Pollutants In Some Freshwater Fishes From Matlab Floodplain Area, Bangladesh (Bangladesh Journal of Zoology, 2012)
The level of organochlorine pesticide residues (OCPs), viz. ?-, ?-, ?-BHC,heptachlor, aldrin, heptachlor epoxide isomer B, dieldrin, 4,4-DDE, endrin, 2,4-DDD, 4,4-DDT, 4,4-DDD, 2,4-DDT in fish samples from Matlab floodplain areas were determined. The fish samples were extracted with ethyl acetate, the extracts were cleaned up by sulphuric acid treatment and analyzed by gas chromatograph (GC) fitted with electron captured detector and gas chromatograph-mass spectrometer (GC-MS). The result showed that none of the studied fishes contained organochlorine pesticide residues but consist some other harmful organic contaminants in tissues. DOI: http://dx.doi.org/10.3329/bjz.v40i1.12899 Bangladesh J. Zool. 40(1): 101-108, 2012